2021
DOI: 10.1111/ssqu.12983
|View full text |Cite
|
Sign up to set email alerts
|

One Bad Apple Spoils the Bunch: Kavanaugh and Change in Institutional Support for the Supreme Court

Abstract: Objective. We analyze the extent to which, if any, institutional support of the U.S. Supreme Court was influenced by the confirmation hearings of Brett Kavanaugh. Methods. We use a nationally representative survey supplemented with an online survey experiment using a hypothetical nominee both conducted shortly after the Senate confirmed Kavanaugh to the bench. Results. We find a strong relationship between negative feelings toward Kavanaugh and support for reform of the Court and confirm the direction of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Study 1 of Carrington and French (2021) reported results from a correlational analysis that “demonstrate[d] a very strong, significant correlation between feelings toward Brett Kavanaugh and diffuse support for the Supreme Court net identified controls” (p. 1488). But such a correlation between two variables net of controls does not permit an inference that one of the variables has changed the mean of the other variable, let alone an inference that the variable has changed this mean in a particular direction.…”
Section: Carrington and French (2021) Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Study 1 of Carrington and French (2021) reported results from a correlational analysis that “demonstrate[d] a very strong, significant correlation between feelings toward Brett Kavanaugh and diffuse support for the Supreme Court net identified controls” (p. 1488). But such a correlation between two variables net of controls does not permit an inference that one of the variables has changed the mean of the other variable, let alone an inference that the variable has changed this mean in a particular direction.…”
Section: Carrington and French (2021) Studymentioning
confidence: 99%
“…Study 2 of Carrington and French (2021) reported results from a randomized experiment in which treatment participants were told (emphasis in the original as reported in the Supplementary Material) that:
Multiple sources within the White House have confirmed that Senator Ted Cruz is the number one choice to fill the next Supreme Court vacancy. According to sources, Cruz, who graduated from a top law program and considers himself to be an originalist when it comes to interpreting the Constitution, will be nominated to fill the next Court vacancy whenever that should occur .
…”
Section: Carrington and French (2021) Studymentioning
confidence: 99%
See 3 more Smart Citations